Analysis of the Determinant Factors of Government Performance - Jouzar Farouq Ishak; Ira Siti Sarah; Sulistia Suwondo (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study is to scrutinize the determinants of provincial government performance. The data is sourced from the Budget Realization Report from the Ministry of Finance and the Report on Rating, and Performance Status of Regional Government Administration by the Ministry of Home Affairs The methods used in testing are linear regression with the ranking and performance status of regional government administration from 30 provinces in Indonesia as a sample. The result of this study indicates that only the degree of decentralization influences provincial government performance. The essence of decentralization is internalizing costs and benefits for the people. To encourage the improvement of regional quality, local governments should integrate all programs and activities with the central government.